2011
DOI: 10.1021/jo102537n
|View full text |Cite
|
Sign up to set email alerts
|

Direct Displacement of Alkoxy Groups of Vinylogous Esters by Grignard Reagents

Abstract: The direct displacement of alkoxy groups from the beta position of aromatic and unsaturated esters and ketones is described. The reaction is chemo- and regioselective, displaying wide substrate scope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
4
17
0
Order By: Relevance
“…Although ketones are generally viewed as incompatible with the high nucleophilicity of Grignard reagents, we have shown that the displacement reaction is facile at temperatures below which the ester or ketone products will undergo addition (Table 1, entries 2–5) 1 . As an exception, MeMgI in CH 2 Cl 2 undergoes complete addition to the carbonyl group as previously reported 31 and confirmed in our lab (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Although ketones are generally viewed as incompatible with the high nucleophilicity of Grignard reagents, we have shown that the displacement reaction is facile at temperatures below which the ester or ketone products will undergo addition (Table 1, entries 2–5) 1 . As an exception, MeMgI in CH 2 Cl 2 undergoes complete addition to the carbonyl group as previously reported 31 and confirmed in our lab (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 93%
“…These theoretical results were not in accordance with the reported reactivity for this substrate, since a slower but still complete chemoselectivity towards methoxy group displacement was previously published. 1 Intrigued by these observations, we repeated the same reactions and re-examined the NMR data of the isolated compounds carefully. Thereafter, we concluded that our previous assessment of reactivity for this compound was wrong, and the ester carbonyl group indeed reacts exclusively to provide the corresponding isopropyl ketone 10 in good yield (85%, Scheme 4), which did not undergo further 1,2-addition.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations